Chronostratigraphy of eastern Mediterranen Sea sediment cores - James SL Casford; Ramadan Abu-Zied; Eelco J Rohling; Steve Cooke; Christophe Fontanier; M Leng; Andrew Millard; J Thomson (PANGAEA, 2007)
An Accelerator Mass Spectrometry (AMS) 14C dated multiparameter event stratigraphy is developed for the Aegean Sea on the basis of highly resolved (centimeter to subcentimeter) multiproxy data collected from four late glacial to Holocene sediment cores. We quantify the degree of proportionality and synchroneity of sediment accumulation in these cores and use this framework to optimize the confidence levels in regional marine, radiocarbon-based chronostratigraphies. The applicability of the framework to published, lower-resolution records from the Aegean Sea is assessed. Next this is extended into the wider eastern Mediterranean, using new and previously published high-resolution data from the northern Levantine and Adriatic cores. We determine that the magnitude of uncertainties in the intercore comparison of AMS 14C datings based on planktonic foraminifera in the eastern Mediterranean is of the order of ±240 years (2 SE). These uncertainties are attributed to synsedimentary and postsedimentary processes that affect the materials dated. This study also offers a background age control that allows for vital refinements to radiocarbon-based chronostratigraphy in the eastern Mediterranean, with the potential for similar frameworks to be developed for any other well-studied region.
Supplement to: Casford, JSL et al. (2007): A stratigraphically controlled multiproxy chronostratigraphy for the eastern Mediterranean. Paleoceanography, 22(4), PA4215, https://doi.org/10.1029/2007PA001422